2017
DOI: 10.1007/s10342-017-1026-7
|View full text |Cite
|
Sign up to set email alerts
|

Does tree-ring formation follow leaf phenology in Pedunculate oak (Quercus robur L.)?

Abstract: We monitored leaf phenology and xylogenesis of 12 Pedunculate oaks in northern Poland in 2014. We hypothesized that the individual trees, which differed in size, age and habitat (tree stand or gap), also diverged in terms of the seasonal patterns of leaf phenology and xylogenesis. The samples used for wood formation observations were collected most frequently during the early leaf phenophases (from March to end of June). The transverse sections of the cambial region were cut with a sledge microtome. We counted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 32 publications
2
40
1
2
Order By: Relevance
“…; Puchałka et al . ). In general, the diameter growth in oak seedlings is favoured by early cambium growth irrespective of the leaf flush receiving an additional advantage in terms of growth, while in beech both cambial growth and leaf flushing occur simultaneously (Čufar et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Puchałka et al . ). In general, the diameter growth in oak seedlings is favoured by early cambium growth irrespective of the leaf flush receiving an additional advantage in terms of growth, while in beech both cambial growth and leaf flushing occur simultaneously (Čufar et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Puchałka et al . ). In general, we expect increased plant growth with warming, which may, however, be limited by water availability during the growing season (Martinez‐Sancho et al .…”
Section: Discussionmentioning
confidence: 97%
“…The earlier development of trees can affect the number and size of early wood vessels due to the early spring temperature [42,43]. The authors [13] observed damage after the sudden frost in May in some individuals of the Pedunculate oak, but they did not validate the hypothesis that the springtime ground frost had a negative effect on either tree-ring width or the number and size of earlywood vessels. The authors [44,45] said that species with late leaf development responded to climate change on average less than species with earlier leaf development.…”
Section: Resultsmentioning
confidence: 90%
“…We used data from the database of the Climatological and Meteorological Information System of the Slovak Hydrometeorological Institute in Bratislava to study the phenological conditions in Slovakia. In order to capture the variability of vegetation during the year, we processed the phenophases of flowering BBCH scale 60, leaves unfolding-BBCH 11 and ripe of fruit-BBCH 86 [13]. We focused on native species: C. avellana (european hazel-COA), C. oxyacantha (hawthorn-CO), P. spinosa L. (blackthorn-PS) and T. cordata (small-leaved lime-TC).…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation